Pengaruh Iklan Obat Batuk pada Media Elektronik Terhadap Pemilihan Obat Swamedikasi - Siti Mujiati; Ika Ratna Hidayati; Rizka Novia Atmadani (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2022)
Introduction: Information about medicines obtained by the public in self-medication can be obtained through advertising. Drug advertisements must contain information that is objective, complete, and not misleading as stipulated in the Regulation of POM. Objective: this research is to know the effect of cough medicine advertisements in electronic media on self-medication selection in the community. Method This study used a cross-sectional method and was conducted in society using an accidental sampling technique. The instrument used in this research is a questionnaire and the analysis technique in this study is using t-test and a simple linear regression test. Result Cough medicine advertisements in electronic media have an influence of 30.5% on the selection of self-medication drugs, while 69.5% is influenced by other factors with the linear equation Y= 2.027 + 0.357x. Conclusion: There is an effect of cough medicine advertisements advertised in electronic media on the selection of self-medication